A STUDY OF CHEMOSENSORY SYSTEMS IN FRESHWATER AND MARINE FISHES OF VIETNAM - A. O., Kasumyan; N. I., Pashchenko; O. M., Isaeva; Le, Thi Kieu Oanh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
The sensory systems of tropical fish remain poorly studied despite the richness and diversity of the tropical ichthyofauna. Studies of the olfactory and gustatory systems in fishes of Vietnam have not been previously carried out. The article for the first time provides information about the morphology of the olfactory organ in several species of freshwater and marine fish of families Anabantidae, Pomacentridae, Labridae, Mullidae. The morphological peculiarities of olfactory cavity, olfactory rosette and lamellae and ventilation olfactory sacs are discussed. Structures previously unknown for the olfactory organ of fish are described for the first time. The mechanisms of ventilation of the olfactory cavity are considered. Data on the effectiveness of natural taste deterrents and their significance in providing chemical protection for marine animals and plants against fish are presented. The relationships between hosts and symbionts in the example of echinoderms and other invertebrates of coral reefs of Vietnam are discussed. How the animal chemical defense and their coloration are related is analyzed. Data on taste preferences in cultivated fish are obtained.